Doing philosophy as a Christian - DeWeese, Garrett J., 1947- (Downers Grove, IL : IVP Academic, 2011)
Noting that philosophy literally is "the love of wisdom," Garrett DeWeese aptly begins with a discussion of wisdom from the Old and New Testaments. He then moves on to reflect on the often misunderstood relation between faith and reason.
Why should you read this book? -- Philosophers and sages : Hokhmah and Sophia -- Philosophy within the limits of religion alone? : faith and reason -- Jesus and philosophy -- What is real? : metaphysics -- What do I know? : epistemology -- What should I value? : ethics and aesthetics -- Who and what am I? : philosophy of mind -- Understanding nature : philosophy of science -- Transforming the soul : philosophy and spiritual formation.
Includes bibliographical references (p. [333]-344) and indexes.
Description based on print version record.
Keywords: Christian philosophy; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books